(untitled) (World Bulletin of Management and Law, 2022)
In this article the opinions of the philosophers of the East and the West about the state administration, comparative analysis of the collected experiences and particular features of the administrative traditions in the history of the Uzbek national statehood are reported. Moreover, the important significance of the political management in providing the stability of the society today is shown by the example of Uzbekistan and the neighboring countries